PENGELOLAAN SAMPAH ORGANIK DAN ANORGANIK UNTUK MENINGKATKAN KREATIVITAS SISWA/I DI PESANTREN DARUL MURSYID - Denny Walady Utama; Zaharuddin Zaharuddin; Abdul Azis Syarif; Budhi Santri Kusuma; Masdania Zurairah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Currently, waste is a very serious environmental problem faced by Indonesian society in general, especially inorganic waste such as plastic bottles, containers or plastic packaging that accumulates causing problems in the environment. Community service activities that have been carried out at Darul Mursyid Islamic Boarding School, lecturers transfer knowledge by providing presentation materials on how to process inorganic waste and how to preserve the environment, makes handicrafts from recycled materials so that it can increase students creativity. The purpose of community service activities is to provide understanding to Darul Mursyid students to maintain and increase environmental knowledge and process recycling waste, especially inorganic waste, into items that can be reused